The Role of the Tourism Department in Maintaining Natal Beach as a Tourism Destination in the Context of Fiqh Siyasah - Niranda Yuniar; Deasy Yunita (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
Beaches are dynamic geographical areas formed by the accumulation of sand, shaped by sea waves, tides, abrasion, and accretion. These natural processes can lead to both temporary and permanent changes, impacting the attractiveness of tourism destinations. This study examines the role of the Tourism Office in managing and maintaining Pantai Natal, located in Kecamatan Natal, Mandailing Natal Regency, and analyzes its efforts through the lens of Fiqh Siyasah. The objectives are to: (1) evaluate the Tourism Office's role in preserving the destination, (2) identify supporting factors and challenges, and (3) assess the alignment of these efforts with Fiqh Siyasah principles. The research employs a combination of field research and normative empirical legal methods. Field research gathers direct data on conditions and task execution, while normative legal analysis reviews relevant regulations, including Presidential Regulation No. 51 of 2016 and Law No. 27 of 2007. Using a qualitative descriptive approach, data is collected through interviews and observations. The findings reveal that the Tourism Office’s efforts are suboptimal, with issues such as damaged facilities, littering, and inadequate attention to historical sites. Positive measures, like enhanced cleanliness, have been implemented, but major barriers remain, including limited budget, insufficient infrastructure, and low community engagement. The study concludes by emphasizing the importance of community involvement and infrastructure development to ensure the sustainable management of Pantai Natal, ultimately maximizing its economic and cultural potential